Diagnostic use of proficiency testing in dairy laboratory - Oto HANUŠ; Václava GENČUROVÁ; Pavel HERING; Miloš KLIMEŠ; Radoslava JEDELSKÁ (Acta Agriculturae Slovenica, 2004)
The composition of raw milk (RM) is important for milk recording, herd improvement, payment of milk and for quality evaluation. The reliability of routine analytical results is therefore significant. A mistake occurrence could jeopardize the efficiency of results. Milk laboratories (ML) perform the systems of analytical quality assurance. Proficiency tests are carried out usually by 10 RM samples with modified variability of components. At evaluation the system of Euclidian distance (Re=(2+sd2)0.5) for participants order according to their analytical result reliability is used. Two specificaly modified types (designs) of systematic diagnostical graphs were constructed on the Re basis. The first type of flow diagnostical diagram for RM analysators is based on Shewhart´s diagram principles for Re parameter (alternating system of result rendering before and after calibrations). The second type is based on analysator set comparisons before (proficiency test results) and after calibration (success of calibration) by Re. The opposite comparison is possible and valuable as well. It makes possible the diagnosis and incidental co-ordinating of the corrections in the case of the unconformity occurrence. The positive contributions of the developed diagnostic graphics system are expected to: – improvement of estimation of unconformity sources of RM routine analytical results, their origin and character; – determination and improvement of incidental result corrections and instrument repairs; – improvement of reliability of routine results of RM analyses in general.